Model-Driven Engineering for ARrupiah Cultural AR App: Kano Model and Qualitative User Experience Evaluation - Gerson Feoh; I Made Dwi Ardiada; Gabriel Firsta Adnyana; I Gede Hendrayana (Informatika, Universitas Jenderal Soedirman, 2026)
The use of Augmented Reality (AR) in learning is becoming increasingly widespread, especially for introducing cultural and historical material in a more interesting way. However, many AR applications are still built without a structured design, making them difficult to develop when content is added. This study uses a Model-Driven Design (MDD) approach to organize the design of the ARrupiah application to make it more modular and easier to expand. After the prototype was completed, testing was conducted through surveys and interviews. The Kano survey involved 50 students to evaluate the main features of the application, while semi-structured interviews were analyzed using NVivo software to explore response patterns and user experiences, with a code saturation level of 80%. The survey results showed that around 70% of the features fell into the Attractive category, with a System Usability Scale (SUS) score of 82/100, indicating ease of use. Qualitative analysis reinforced the quantitative results through a triangulation process, in which features categorized as Attractive also emerged as a dominant theme of visual engagement in the NVivo results. This combined approach strengthens the validity of the findings and provides a more comprehensive understanding of user perceptions and satisfaction. Overall, the application of MDD not only helps refine the technical design but also improves the quality of the learning experience through ARrupiah-based interactive media.